Reformasi Sistem Penjara Untuk Mengatasi Overkapasitas Rumah Tahanan : Tinjauan Dari Sudut Pandang Hukum Nasional : ( Studi Kasus Rumah Tahanan Kebon Waru Bandung) (International Forum of Researchers and Lecturers, 2023)
Prison overcrowding has become a serious issue in Indonesia. This phenomenon occurs when the number of detainees exceeds the maximum capacity available in prisons and correctional institutions. The objective of this research is to analyze the background of prison overcrowding in Indonesia.Prison overcrowding has become a serious issue in Indonesia. This phenomenon occurs when the number of detainees exceeds the maximum capacity available in prisons and correctional institutions. The objective of this research is to analyze the background of prison overcrowding in Indonesia. The problem approach in this research utilizes both normative legal and empirical legal approaches. The normative legal approach is intended to understand the issue while remaining within the framework of legal principles, while the empirical legal approach aims to gain clarity and understanding of the research issue based on existing realities.Overcrowded prisons have various negative impacts, both on the detainees themselves and on the criminal justice system. First, the excess number of detainees leads to an increased risk of violence, conflicts, and security disturbances within the prison. This affects the well-being and safety of both detainees and security personnel. Second, overcrowding also affects the quality of life for detainees. Limited capacity means that resources such as food, water, beds, healthcare facilities, and access to education and rehabilitation are insufficient for all detainees.